(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A simple, Accurate, precise method was developed for the simultaneous estimation of the Cabotegravir and Rilpivirine in pharmaceutical dosage form. Chromatogram was run through Hibar C18 100 x 2.1 mm, 2m. Mobile phase containing Water: Acetonitrile taken in the ratio 55:45 was pumped through column at a flow rate of 0.3 ml/min. Temperature was maintained at 30°C. Optimized wavelength selected was 257 nm. Retention time of RPN and CGV were found to be 0.618 min and 1.152. %RSD of the CGV and RPN were found to be 0.3 and 1.5 respectively. %Recovery was obtained as 99.79% and 99.58% for CGV and RPN respectively. LOD, LOQ values obtained from regression equations of CGV and RPN were 0.43, 1.30 and 0.78, 2.37 respectively. Regression equation of CGV is y = 4028.3x + 977.59, and RPN is y = 4057.2x + 1673.2. Retention times were decreased and that run time was decreased, so the method developed was simple and economical that can be adopted in regular Quality control test in Industries.